2015
DOI: 10.14419/ijans.v4i2.4738
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of paternal perinatal depressive mood and its relationship with maternal depression symptomatology: An Italian study

Abstract: <p><strong>Background:</strong> Literature shows that the birth of a child is a vulnerability moment for the mental well-being of both parents.</p><p><strong>Objectives:</strong> estimate the prevalence of a depressive symptomatology in an Italian sample of new fathers during the first six months postpartum and provide its association with maternal mood.</p><p><strong>Methods:</strong> 244 neo- parents filled the Italian version of the Edinburgh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…3) with substantial heterogeneity (I 2 =97.78%); (Anding et al, 2016;Bergström, 2013;Bielawska-Batorowicz & Kossakowska-Petrycka, 2006;Buist et al, 2002;Condon et al, 2004;deMontigny et al, 2013;Dudley et al, 2001;Escribà-Agüir & Artacoz, 2011;Gawlik et al, 2013;Greenhalg et al, 2000;Leathers & Kelly, 2000;Nath et al, 2016;Nishimura et al, 2015;Roubinov et al, 2013, Top et al, 2016 Hall & Long, 2007;Koh et al, 2014;Matthey et al, 2000;Ngai & Ngu, 2015;Ramchandani et al, 2008;Soliday et al, 1999;Suto et al, 2016). History of psychiatric illness was associated with a more than three-fold increase in the likelihood of paternal depression (OR =3.30, 95% CI (1.95-5.57) with substantial heterogeneity (I 2 =87.36%); (Areias, 1996;Bronte-Tinkew et al, 2007;Cattaneo et al, 2015;Nishimura & Ohashi, 2010;Nishimura et al, 2015;Ramchandani et al, 2008;Suto et al, 2016). Alcohol abuse was associated with a more than two-fold increase in the likelihood of paternal depression (OR = 2.40, 95% CI Moreover, paternal postnatal depression and unplanned pregnancy, parenting stress, and preference for a male baby were positively associated with each other in the current meta-analysis.…”
Section: Associations Between Paternal Perinatal Depression and Risk Factorsmentioning
confidence: 99%
“…3) with substantial heterogeneity (I 2 =97.78%); (Anding et al, 2016;Bergström, 2013;Bielawska-Batorowicz & Kossakowska-Petrycka, 2006;Buist et al, 2002;Condon et al, 2004;deMontigny et al, 2013;Dudley et al, 2001;Escribà-Agüir & Artacoz, 2011;Gawlik et al, 2013;Greenhalg et al, 2000;Leathers & Kelly, 2000;Nath et al, 2016;Nishimura et al, 2015;Roubinov et al, 2013, Top et al, 2016 Hall & Long, 2007;Koh et al, 2014;Matthey et al, 2000;Ngai & Ngu, 2015;Ramchandani et al, 2008;Soliday et al, 1999;Suto et al, 2016). History of psychiatric illness was associated with a more than three-fold increase in the likelihood of paternal depression (OR =3.30, 95% CI (1.95-5.57) with substantial heterogeneity (I 2 =87.36%); (Areias, 1996;Bronte-Tinkew et al, 2007;Cattaneo et al, 2015;Nishimura & Ohashi, 2010;Nishimura et al, 2015;Ramchandani et al, 2008;Suto et al, 2016). Alcohol abuse was associated with a more than two-fold increase in the likelihood of paternal depression (OR = 2.40, 95% CI Moreover, paternal postnatal depression and unplanned pregnancy, parenting stress, and preference for a male baby were positively associated with each other in the current meta-analysis.…”
Section: Associations Between Paternal Perinatal Depression and Risk Factorsmentioning
confidence: 99%
“…Recent studies have reported the negative effect of men's adjustment problems during the transition to parenthood on women's adjustment and parenting and mainly on infant development, highlighting the importance of considering both women and men's adjustment to the transition to parenthood to conceptualise the health of the family (e.g. Cattaneo et al, 2015;Gutierrez-Galve et al, 2015;Ramchandani et al, 2011). The results of the present study may provide relevant information for practice and research in prenatal and postpartum mental health.…”
Section: Implications For Clinical Practice and Researchmentioning
confidence: 60%
“…Recent studies have also reported the negative effect of men's adjustment problems during the transition to parenthood on women's adjustment and parenting and mainly on infant development. These studies suggested that when men reveal adjustment problems in the transition to parenthood their partners show more psychopathological symptoms, more negative attitudes towards pregnancy and the baby, and poor mother-infant interaction (Cattaneo et al, 2015;Gutierrez-Galve, Stein, Hanington, Heron, & Ramchandani, 2015;Ramchandani et al, 2011). Altogether, this evidence highlights the importance of considering both women's and men's adjustment to the transition to parenthood to conceptualise the adjustment and health of the family.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Growing evidence shows that fathers' emotions are intrinsically influenced by their partner's mood. First-time fathers may experience depressive symptoms in the immediate postpartum when they are most attuned to maternal mood changes (Cattaneo, 2015). A strong predictor of PPPD is MPPD; between 24% and 50% of men, whose partners have MPPD, experience PPPD compared with 1·2% to 25·5% of men experiencing PPPD whose partners do not have depression (Goodman et al, 2004).…”
Section: Paternal Depressionmentioning
confidence: 99%